2020
DOI: 10.1101/2020.07.08.194019
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Unlocking the Predictive Power of Heterogeneous Data to Build an Operational Dengue Forecasting System

Abstract: Predicting an infectious disease can help reduce its impact by advising public health interventions and personal preventive measures. While availability of heterogeneous data streams and sensors such as satellite imagery and the Internet have increased the opportunity to indirectly measure, understand, and predict global dynamics, the data may be prohibitively large and/or require intensive data management while also requiring subject matter experts to properly exploit the data sources (e.g., deriving… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 38 publications
(42 reference statements)
0
3
0
Order By: Relevance
“…Our spatial clustering results can provide direction in how to incorporate current and historical spatial information in an informed and efficient way. Finally, our results also revealed that broad capturing and integration of disparate data streams are beneficial for explaining disease dynamics, and their utility in forecasting systems should continue to be explored [ 9 , 10 ]. Here, we found that an individual time series data stream, such as temperature, can be used in numerous ways, whether as a standard summary statistic (e.g., mean), or as more complex dynamic measurements (e.g., intensity).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Our spatial clustering results can provide direction in how to incorporate current and historical spatial information in an informed and efficient way. Finally, our results also revealed that broad capturing and integration of disparate data streams are beneficial for explaining disease dynamics, and their utility in forecasting systems should continue to be explored [ 9 , 10 ]. Here, we found that an individual time series data stream, such as temperature, can be used in numerous ways, whether as a standard summary statistic (e.g., mean), or as more complex dynamic measurements (e.g., intensity).…”
Section: Discussionmentioning
confidence: 99%
“…Environmental data. From a previously published environmental data set for Brazil [9,10], we collected time series of five satellite remote sensing indices (Table 1: green Normalized Difference Water Index (green NDWI), short-wave infrared Normalized Difference Water Index (SWIR NDWI), Normalized Burn Ratio (NBR), Normalized Difference Vegetation Index (NDVI), and % cloudy pixels), and three climatic weather variables (Table 1: daily range in temperature, mean temperature, and relative humidity). Satellite remote sensing data from January 2010 to December 2016 were derived from the multispectral satellites Landsat 5, Landsat 7, Landsat 8, and Sentinel-2, and the source images were accessed via the Descartes Labs Platform [31].…”
Section: Datamentioning
confidence: 99%
See 1 more Smart Citation